Training on Making Trash Bins from Used Gallons to Promote Waste Sorting Habits among Students at SMP Kanzul Ulum - Ila Magfiroh; Muhyati Muhyati; Meilan Dwi Ferdiana; Frisca Adilah Khoiri; Siti Eneng Sururiyatul Mu'aziyah (CV. Dharma Samakta Edukhatulistiwa, 2026)
The waste problem in Indonesia, especially plastic waste, remains an environmental issue and requires early intervention through education in schools. One of the problems at Kanzul Ulum Middle School is the limited availability of trash bins and the low level of waste sorting habits. This community service activity aims to increase awareness and habits in waste sorting through training on making trash bins from used gallon jugs. The implementation method consists of socializing the trash bin service activity from gallon jugs, training on making trash bins, and evaluating the success of the training/implementation in learning. This community service activity was attended by all students in grades VII, VIII, and IX of Kanzul Ulum Middle School. The results of the community service activity showed an increase in students' enthusiasm, creativity, and understanding of the types of waste and how to sort them. In addition to producing products in the form of trash bins that can be used directly in the school environment, this activity can encourage the formation of an attitude of caring for the environment in students. Thus, the training on making trash bins from used gallon jugs provides an educational solution to support waste management.